2021
DOI: 10.1177/016146812112300104
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Shifts in and Out of the Classroom: Dynamics of Teacher Salary and Teacher Supply in Urban China

Abstract: Background The remarkable economic growth in contemporary China is unprecedented, but scholars voice concerns regarding unintended consequences during this transitional phase. Of particular concern is the constant challenge to staff schools with highly qualified teachers. Purpose This study sets out to understand subtle yet consequential changes in schools during a sustained period of economic boom, through the lens of teacher occupational choice. This study contributes empirically to the teacher occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…On the whole: findings in the present study contribute new evidence to a large cluster of studies highlighting the importance of teacher education (Liu and Xie 2021) and that more qualified individuals are also more likely to be competent and effective in meeting a variety of instructional needs (Loeb et al 2014). While some scholars question the usefulness of policies aimed at improving teacher education and increasing teacher educational attainment, findings in this present study refute such doubts by illuminating the significant and substantive cognitive returns associated with having better educated teachers.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…On the whole: findings in the present study contribute new evidence to a large cluster of studies highlighting the importance of teacher education (Liu and Xie 2021) and that more qualified individuals are also more likely to be competent and effective in meeting a variety of instructional needs (Loeb et al 2014). While some scholars question the usefulness of policies aimed at improving teacher education and increasing teacher educational attainment, findings in this present study refute such doubts by illuminating the significant and substantive cognitive returns associated with having better educated teachers.…”
Section: Discussionsupporting
confidence: 74%
“…Coinciding with rising policy attention in attracting talented individuals to join the teacher workforce, teacher education researchers and teacher policy makers have become increasingly interested in understanding how observable traits are related to student learning improvements (Liu and Xie 2021). In theoretical terms, holding a higher level of educational attainment can imply either a better state of a teacher's own level of human capital development, or can act as a positive signal of adept innate ability, academic motivation, and cognitive skills development compared to those teachers without such credentials.…”
Section: Introductionmentioning
confidence: 99%
“…Vagi (2019) analyzed data from apprenticeship teacher preparation programs and found that more qualified student teachers were more likely to enter and remain in the profession. In addition, Liu's (2021) findings highlight the critical role of teachers' salary growth and human capital returns on career decisions. García's (2022) research revealed a positive relationship between teachers' basic salary and students' academic performance.…”
Section: Topic 2: Teacher Training and Professional Developmentmentioning
confidence: 93%